Biogeochemistry of Dissolved Organic Matter in Pony Lake, Ross Island - Chin, Yu-Ping; Foreman, Christine (IEDA: US Antarctic Program Data Center, 2009)
Dissolved organic matter (DOM) is a significant chemical component in aquatic systems because it acts as an important carbon source for microorganisms, absorbs harmful radiation in sunlight, is able to complex metals, and can participate in important biogeochemical reactions. This study will investigate the biogeochemical cycling of DOM in a small coastal Antarctic pond, Pony Lake, located on Cape Royds, Ross Island. Because there are no higher plants present at this site all of the DOM in this lake is derived from microorganisms. Thus, Pony Lake is an ideal site to study the effect of physical, chemical, and microbial processes on the composition and character of the DOM pool. Finally, Pony Lake is also an ideal site to collect an International Humic Substances Society (IHSS) fulvic acid standard. Unlike other IHSS standards, this standard will not contain DOM components derived from higher land plants. To better understand the role of physical influences, the project will study the changes in the DOM pool as the lake evolves from ice-covered to ice-free conditions during the summer, as well as the relationship of DOM to the observed turnover of dominant microbial communities in the lake. Scientists will also monitor changes in microbial abundance, diversity, and productivity that may occur during the ice to open-water transition period. This research will provide much needed information regarding the relationship between microbial diversity and DOM biogeochemistry. Middle school science students will be active participants in this project through the Internet, while scientists are in the field, and in the lab.